Primitive Culture: Researches into the Development of Mythology, Philosophy, Religion, Art, and Custom: volume 2 - Tylor, Edward B. (John Murray, 1920)
Edward Burnett Tylor (1832–1917) was an English anthropologist who is widely considered the founder of anthropology as a scientific discipline. He was the first Professor of Anthropology at the University of Oxford from 1896 to 1909, and developed a broad definition of culture which is still used by scholars. First published in 1871, this classic work explains Tylor's idea of cultural evolution in relation to anthropology, a social theory which states that human cultures invariably change over time to become more complex. Unlike his contemporaries, Tylor did not link biological evolution to cultural evolution, asserting that all human minds are the same irrespective of a society's state of evolution. His book was extremely influential in popularising the study of anthropology and establishing cultural evolution as the main theoretical framework followed by anthropologists in the nineteenth and early twentieth centuries. Volume 2 contains Tylor's interpretation of animism in society.
free